Remittances in Latin America: Trends and Persistence - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana; Karen Roxana Quinatoa Narváez (CESifo GmbH, 2024)
This paper analyses remittances in fifteeen Latin American countries (Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Ecuador, El Salvador, Guatemala, Haiti, Honduras, Panama, Dominican Republic, Uruguay and Venezuela) by applying fractional integration methods to World Bank annual data. The start year varies from 1970 in Colombia and Venezuela to 2003 in Uruguay, while the end year is 2022 in all cases except Venezuela, for which it is 2016. The chosen approach provides evidence on trends and persistence in the series under investigation. The results indicate that the effects of shocks to remittances are transitory only in Guatemala and Honduras. This might reflect the rather stable employment and wages of migrant workers from these two countries residing in the US, cultural factors, and the relatively small values and/or low volatility of remittances to these two countries.
Keywords: C22; G20; 330; remittances; time trends; persistence; fractional integration